TINJAUAN YURIDIS AKIBAT HUKUM PUTUSAN MAHKAMAH KONSTITUSI NOMOR 69/PUU-XIII/2015 - sinambela, delvy may nita; Svinarky, Irene (LPPM Universitas Putera Batam, 2021)
Then an agreement was concluded with shared ownership. The prenuptial contract is a contract that is concluded before the marriage of two individuals (betrothed couple). Article 29 of Law no. 1 of 1974 provided for the Prenuptial Agreement. However, the Prenuptial Agreement has many changes which are now in the interests of society and are inconvenient since Decision No. 69/PUU-XIII/2015 has been issued by the Constitutional Court. The question revised in this theory is: what is the legal effect of a marital prenuptial contract on the basis of Decision No 69/PUU-XIII/2015 of the Constitutional Court. Normative legal research is the methodology that is utilized here. The material source of the law is in the form of books and law material from primary law and secondary law. The data analyzes utilized in this study are qualitatively and descriptively developed for the processing and analysis of data. According to the findings of this research, there are differences between the Prenuptial Agreement provided for in Article 29 of Law No. 1 of 1974 and the Prenuptial Agreement provided for by Decision No. 79/PUU-XIII/2015.